Clinical and genetic spectrum of 6 cases with asparagine synthetase deficiency - Song, P P (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2024)
Objective: To explore the clinical and genetic characteristics of asparagine synthase deficiency. Methods: Case series studies. Retrospective analysis and summary of the clinical data of 6 cases with asparagine synthase deficiency who were diagnosed by genetic testing and admitted to the Third Affiliated Hospital of Zhengzhou University from May 2017 to April 2023 were analyzed retrospectively. The main clinical features, laboratory and imaging examination characteristics of the 6 cases were summarized, and the gene variation sites of them were analyzed. Results: All of the 6 cases were male, with onset ages ranging from 1 month to 1 year and 4 months. All of the 6 cases had cognitive and motor developmental delay, with 3 cases starting with developmental delay, 3 cases starting with convulsions and later experiencing developmental arrest or even regression. All of 6 cases had epilepsy, in whom 2 cases with severe microcephaly developed epileptic encephalopathy in the early stages of infancy with spasms as the main form of convulsions, 4 cases with mild or no microcephaly gradually evolved into convulsions with no fever after multiple febrile convulsions with focal seizures, tonic clonic seizures and tonic seizure as the main forms of convulsions. Three cases of 4 gradually developed into stagnation or even regression of development and ataxia after multiple convulsions with no fever. There were normal cranial imaging in 2 cases, dysplasia of the brains in 1 cases, frontal lobe apex accompanied by abnormal white matter signal in the frontal lobe and thin corpus callosum in 1 case, thin corpus callosum and abnormal lateral ventricular morphology in 1 case, and normal in early stage, but gradually developing into cerebellar atrophy at the age of 5 years and 9 months in 1 case. Two cases underwent visual evoked potential tests, the results of which were both abnormal. Three cases underwent auditory evoked potential examination, with 1 being normal and 2 being abnormal. All of 6 cases had variations in the asparagine synthase gene, with 2 deletion variations and 7 missense variations. The variations of 2 cases had not been reported so far, including c.1341_1343del and c.1283A>G, c.1165_1167del and c.1075G>A. The follow-up time ranged from 3 months to 53 months. Two cases who had severe microcephaly died in infancy, while the other 4 cases with mild or no microcephaly were in survival states until the follow-up days but the control of epilepsy was poor. Conclusions: Asparagine synthase deficiency has a certain degree of heterogeneity in clinical phenotype. Children with obvious microcephaly often present as severe cases, while children with mild or no microcephaly have relatively mild clinical manifestations. The variation of asparagine synthetase gene is mainly missense variation